CFD Analysis of a Decay Tank and a Siphon Breaker for an Innovative Integrated Passive Safety System for a Research Reactor - Kwon-Yeong Lee; Hyun-Gi Yoon; Dong Kyou Park (Science and Technology of Nuclear Installations)
An innovative integrated passive safety system for a research reactor is proposed in this study to improve the safety of the research reactor. This integrated system has three functions in the facility as a decay tank, siphon breaker, and long-term cooling tank. This paper also deals with the process of designing and optimizing the decay tank and the siphon breaker of the integrated passive safety system. At first, the decay tank was designed and improved step by step, while considering the computational fluid dynamics analysis results. Consequently, we could satisfy the design requirements of the decay tank. In addition, the performance of a new type of siphon breaker that was installed in the final decay tank model was tested. We designed an 18-inch diameter siphon breaker at the top of the decay tank’s third section, and we could observe the breaking of the siphon that prevented the occurrence of a severe accident in the research reactor. By locating the siphon breaker at the third section of the decay tank, we could also use the coolant of the front three sections for long-term cooling of the research reactor.